2019
DOI: 10.3390/cancers11010121
|View full text |Cite
|
Sign up to set email alerts
|

The Oncogene Addiction Switch from NOTCH to PI3K Requires Simultaneous Targeting of NOTCH and PI3K Pathway Inhibition in Glioblastoma

Abstract: The NOTCH pathway regulates neural stem cells and glioma initiating cells (GICs). However, blocking NOTCH activity with γ-secretase inhibitors (GSIs) fails to alter the growth of GICs, as GSIs seem to be active in only a fraction of GICs lines with constitutive NOTCH activity. Here we report loss of PTEN function as a critical event leading to resistance to NOTCH inhibition, which causes the transfer of oncogene addiction from the NOTCH pathway to the PI3K pathway. Drug cytotoxicity testing of eight GICs showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 32 publications
(34 reference statements)
1
18
0
Order By: Relevance
“…Considering the extensive intertumoral heterogeneity in glioma, it is possible that NOTCH inhibition would be beneficial only in a proportion of molecularly selected patients in a personalized therapy. For instance, studies in vitro suggest that PTEN and TP53 status may affect sensitivity to GSIs in GBM [ 156 , 157 ]. NOTCH and EGF receptor pathways can potentiate each other in glioma cells [ 158 , 159 , 160 ] and, therefore, the oncogenic function of NOTCH signaling could be more apparent in primary GBMs of the classical subtype [ 161 ] than in GBMs with OPC-like proneural features [ 162 ] or IDH mutant LGGs [ 24 , 25 ].…”
Section: Open Questions and Perspectivesmentioning
confidence: 99%
“…Considering the extensive intertumoral heterogeneity in glioma, it is possible that NOTCH inhibition would be beneficial only in a proportion of molecularly selected patients in a personalized therapy. For instance, studies in vitro suggest that PTEN and TP53 status may affect sensitivity to GSIs in GBM [ 156 , 157 ]. NOTCH and EGF receptor pathways can potentiate each other in glioma cells [ 158 , 159 , 160 ] and, therefore, the oncogenic function of NOTCH signaling could be more apparent in primary GBMs of the classical subtype [ 161 ] than in GBMs with OPC-like proneural features [ 162 ] or IDH mutant LGGs [ 24 , 25 ].…”
Section: Open Questions and Perspectivesmentioning
confidence: 99%
“…Moreover, the relationship between the Notch, Wnt, and PI3K downstream genes is previously identified (50). Recently, Norihiko Saito and colleagues have reported that GSI resistance results from a change in oncogene addiction, from NOTCH to constitutive AKT in glioblastoma, and that the combination of GSIs and PI3K inhibitors may reduce tumor growth in glioblastoma (51).…”
Section: Discussionmentioning
confidence: 99%
“…Some recent data suggest that one mechanism may be connected with the downregulation of PTEN by activated NOTCH [56]. In some malignancies such as acute T-cell lymphoblastic leukemia, activation of the PI3K/AKT pathway downstream of NOTCH1 signaling promotes cell proliferation at multiple levels and has an important role in T-cell transformation [56,57]. Analysis of the transcriptional responses of GSI-sensitive PTEN wild-type glioblastoma cells to NOTCH inhibition showed significant upregulation of PTEN expression.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of the transcriptional responses of GSI-sensitive PTEN wild-type glioblastoma cells to NOTCH inhibition showed significant upregulation of PTEN expression. The authors demonstrated one possible mechanism of PTEN downregulation in vitro, which was mediated by HES1-a transcriptional repressor directly controlled by NOTCH [57].…”
Section: Discussionmentioning
confidence: 99%